Visual Improvement of Slums: Integrative Strategy for Optimizing Sanitation Management Sustainability in Slum Areas - Novanta, Muhammad Iqbal; Soewondo, Prayatni (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
The high population growth rate in certain areas is a critical problem confronting big cities in Indonesia, which in turn creates pressure on urban governance, thus creating slum areas. Until now, insufficient funds are still a problem in alleviating the problem of slums, so the concept of visual improvement is a program that has been proposed to serve as a form of capital in fostering community participation in managing the surrounding environment. This study aimed to identify the impact of visual improvement programs in two slum areas, related to sanitation management, in particular domestic wastewater management and solid waste management. The two slum areas have different settlement typologies. Bekelir Rainbow Village, Tangerang is a slum settlement in the lowlands, and Code Rainbow Village, Yogyakarta is a slum settlement on the banks of a river. The success of the visual improvement programs was identified by factors that underlie the behavior of sanitation management and its relationship with the Theory of Planned Behavior construct. After the successfulness of the programs had been identified, the next step was to identify the sustainability factors for sanitation management so that strategies for optimizing sanitation management can be planned to support the sustainability of sanitation management as the basis for future visual improvement programs of slum areas. By using the Structural Equation Modeling method, it was found that institutional regulatory aspects as well as financial-economic aspects were the most influential aspects related to sustainability of domestic wastewater and solid waste management in Bekelir Rainbow Village, Tangerang. Meanwhile, socio-cultural aspects as well as regulatory-institutional aspects were the most influential aspects related to sustainability of domestic wastewater and solid waste management in Code Rainbow Village, Yogyakarta. This indicates that the strategies for optimizing sanitation management in the two rainbow villages had a different approach.